Inoperable Pancreatic Cancer Patients Who Have Prolonged Survival Exhibit an Increased Risk of Cholangitis - Buxbaum, James L; Biggins, Scott W; Bagatelos, Karen C; Inadomi, John M; Ostroff, James W (JOP. Journal of the Pancreas, 2011)
Context Endoscopically placed metal stents, which are patent for 4-9 months, have been the favored decompressive strategy for biliary obstruction due to inoperable pancreatic cancer in order to minimize interventions. However, in the past decade chemotherapeutic options have improved survival. This raises the question of whether metal stents will continue to be the optimal method of decompression. Objective We performed a study to determine the outcome of patients with non-operatively managed pancreatic adenocarcinoma with regards to the development of cholangitis. Design We reviewed all ERCP performed for malignant distal biliary obstruction in between December 1999 and December 2005 at University of California, San Francisco (UCSF). Patients Only patients who received chemotherapy for pancreatic adenocarcinoma were included. Patients who underwent surgical biliary diversion procedures were excluded. Primary outcome measurement The primary outcome was the development of cholangitis requiring hospitalization. Results Among 200 patients with malignant distal biliary obstruction who underwent endoscopic biliary decompression procedures, 54 met study criterion. Metal stents were employed in 90.7% of these cases. The median survival of this population was 12.7 months (range: 2.6-34.6 months). Only 3 of 26 patients (11.5%) surviving one year or less developed cholangitis compared to 13 of 28 (46.5%) who survived more than one year. Thus patients surviving greater than one year had a five fold increase in the odds of developing cholangitis (odds ratio: 4.92; P=0.017). Conclusions This cohort of inoperable pancreatic cancer patients undergoing chemotherapy survived longer than the expected patent period of metal stents employed for biliary decompression. The occurrence of cholangitis requiring hospitalization does increase markedly among long term survivors. Image: Number of patients who survived.